2014
DOI: 10.1371/journal.pone.0112616
|View full text |Cite
|
Sign up to set email alerts
|

Regional Difference in Sex Steroid Action on Formation of Morphological Sex Differences in the Anteroventral Periventricular Nucleus and Principal Nucleus of the Bed Nucleus of the Stria Terminalis

Abstract: Sex steroid action is critical to form sexually dimorphic nuclei, although it is not fully understood. We previously reported that masculinization of the principal nucleus of the bed nucleus of the stria terminalis (BNSTp), which is larger and has more neurons in males than in females, involves aromatized testosterone that acts via estrogen receptor-α (ERα), but not estrogen receptor-β (ERβ). Here, we examined sex steroid action on the formation of the anteroventral periventricular nucleus (AVPV) that is large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…In addition, the volume and neuron numbers of the AVPV in ERα knockout male mice become similar to those in female mice compared with wild-type male mice (Kanaya et al, 2014). In contrast, there is no significant effect of lacking the ERβ gene on the sexually dimorphic formation of the BNSTp and AVPV (Kanaya et al, 2014;Tsukahara et al, 2011). However, there are reports showing that administration of an ERβ agonist, as well as an ERα agonist, into postnatal females has a pharmacological effect to increase the number of BNSTp neurons in mice (Hisasue et al, 2010) and decrease the number of AVPV neurons in rats (Patchev et al, 2004).…”
Section: Contribution Of Sex Steroids To the Sexually Dimorphic Formamentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the volume and neuron numbers of the AVPV in ERα knockout male mice become similar to those in female mice compared with wild-type male mice (Kanaya et al, 2014). In contrast, there is no significant effect of lacking the ERβ gene on the sexually dimorphic formation of the BNSTp and AVPV (Kanaya et al, 2014;Tsukahara et al, 2011). However, there are reports showing that administration of an ERβ agonist, as well as an ERα agonist, into postnatal females has a pharmacological effect to increase the number of BNSTp neurons in mice (Hisasue et al, 2010) and decrease the number of AVPV neurons in rats (Patchev et al, 2004).…”
Section: Contribution Of Sex Steroids To the Sexually Dimorphic Formamentioning
confidence: 81%
“…The volume and neuron numbers of the BNSTp in male mice are decreased by deletion of the ERα gene and become similar to those in female mice (Tsukahara et al, 2011). In addition, the volume and neuron numbers of the AVPV in ERα knockout male mice become similar to those in female mice compared with wild-type male mice (Kanaya et al, 2014). In contrast, there is no significant effect of lacking the ERβ gene on the sexually dimorphic formation of the BNSTp and AVPV (Kanaya et al, 2014;Tsukahara et al, 2011).…”
Section: Contribution Of Sex Steroids To the Sexually Dimorphic Formamentioning
confidence: 84%
“…We demonstrate that CRFR1 cells at P0 co‐express ERα, while previous work has shown that the P0 AVPV/PeN is largely devoid of ERβ (Zuloaga, Zuloaga, Hinds, Carbone, & Handa, ). In addition, androgen receptor (AR) levels are barely detectable at P0 (Juntti et al, ; Kanaya et al, ). Apoptosis is potentially responsible for the observed sex difference in the AVPV as others have shown that perinatal androgen secretions trigger cell death in the developing AVPV (Forger et al, ; Kelly, Varnum, Krentzel, Krug, & Forger, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, incomplete masculinization of the MeA may cause an improper functioning of the neural circuitry for the expression of male-type social behaviors. Testosterone and/or estradiol are involved in development of sexually dimorphic brain morphology by promoting cell proliferation, differentiation, or survival, or by inducing apoptosis in a sex-specific manner in certain brain regions (41)(42)(43)(44)(45). However, the exact mechanisms of ERα-mediated action of testosterone for full masculinization of the MeA structure and function during the pubertal period still remain unknown and need to be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%